Business ethics from tawhidic paradigm - Mhd. Sarif, Suhaimi (2021)
Business Ethics is a functional knowledge in business management studies with the objective to educate students with ethical philosophy, knowledge, and skills. Ethics is not a taught course, but there is a need to expose students to ethical values in business. The foundation of conventional Business Ethics is based on rationality philosophical values. This lecture offers Business Ethics from Tawhidic paradigm, a philosophy of ethics from Quran and Hadith, the primary reference in Islamic teachings. At the end of the lecture, learners should be able to explain the meaning of Tawhidic paradigm, able to apply Tawhidic paradigm into business operations, and able to discuss the influence of Tawhidic paradigm into decisions and actions.